Extensive Causative Esophagitis Caused by Thermal Injury: A Case Report and Review of the Literature - Cherng Harng Lim; Hsu-Heng Yen; Wei-Wen Su; Cherng-Jyr Lim; Hao-Chien Tsai; Shi-Ting Chen (Case Reports in Gastrointestinal Medicine)
Esophagus thermal injury is a rare case that can be easily overlooked by practitioners. We herein present a case of thermally induced diffuse corrosive esophagitis with complaints of dysphagia and retrosternal chest pain after having steamed pork. A thorough disease course was demonstrated by serials of endoscopy images and video. A comprehensive review of articles and a concise overview of esophageal thermal injury clinical manifestation, disease process, typical endoscopy features, pharmacomanagement option, and outcomes will be conducted in this article.